2020
DOI: 10.1038/s41598-020-73836-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrent stroke and antiplatelet choice in breakthrough stroke while on aspirin

Abstract: Uncertainty regarding an optimal antiplatelet regimen still exists in patients with breakthrough acute ischemic stroke (AIS) while on aspirin. This study provides an analysis of a prospective multicenter registry between April 2008 and April 2014. Eligible patients were on aspirin at the time of AIS and treated with antiplatelet regimens (aspirin, clopidogrel, or clopidogrel-aspirin). Potential factors associated with the choice of each antiplatelet regimen were explored and included a predictive risk score fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Despite the efforts of researchers and pharmaceutical companies, the risk of stroke recurrence remains high ( 19 ). The use of antiplatelet agents is recommended to reduce the long-term risk of non-cardioembolic ischemic stroke or TIA ( 20 ). Aspirin is a commonly used antiplatelet agent for secondary stroke prevention, but its benefit must be weighed against its bleeding risks, particularly in the aging population ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the efforts of researchers and pharmaceutical companies, the risk of stroke recurrence remains high ( 19 ). The use of antiplatelet agents is recommended to reduce the long-term risk of non-cardioembolic ischemic stroke or TIA ( 20 ). Aspirin is a commonly used antiplatelet agent for secondary stroke prevention, but its benefit must be weighed against its bleeding risks, particularly in the aging population ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of antiplatelet agents is recommended to reduce the long-term risk of non-cardioembolic ischemic stroke or TIA ( 20 ). Aspirin is a commonly used antiplatelet agent for secondary stroke prevention, but its benefit must be weighed against its bleeding risks, particularly in the aging population ( 20 ). It has been proved that aspirin is safe and beneficial in preventing stroke recurrence, but aspirin can only reduce recurrent vascular events by 20% ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a trend of radical antiplatelet therapy was shown during the period of the guideline update. Kim et al [ 28 ] reported that a large atherosclerotic burden might affect the selection of a combination of DAPT. Similarly, the large-artery atherosclerosis patients in our study were likely to be treated positively.…”
Section: Discussionmentioning
confidence: 99%
“…4. Subjects, predicted in the low-risk profile of recurrent stroke, Essen stroke risk scores ≤ 3 points; [ 15 ]…”
Section: Methodsmentioning
confidence: 99%
“…4. Subjects, predicted in the low-risk profile of recurrent stroke, Essen stroke risk scores ≤ 3 points; [15] 5. Only taking single antiplatelet drug, not overlapping the use of activating blood and removing stasis herbs medicine;…”
Section: Study Population 231 Inclusion Criteria 1subjects Diagnosed ...mentioning
confidence: 99%